Sectoral co-movements of employment growth at regional level. Issue 1 (2nd January 2017) - Capasso, Marco; Frenken, Koen; Treibich, Tania
ABSTRACT: This paper presents a comprehensive study of sectoral co-movements of employment growth in the entire Dutch economy. We construct different macro typologies according to manufacturing versus services, innovativeness, labour skills and position in the value chain, thus expanding the list of potential logics of sectoral interrelations. Using a vector autoregression model, we assess whether and how growth in a macro-sector, and in a given region, can predict growth in the same or other macro-sectors, in the same or in other regions. Our findings bring to light the inter-regional nature of intersectoral linkages, as well as the existence of complementarities between sectors. Supporting the growth of innovative firms could have positive externality effects, especially in the Knowledge-Intensive Business Services sector which is associated with the growth of the entire economy.